Pengaruh Profitabilitas, Good Corporate Governance dan Tipe Industri terhadap Pengungkapan Sustainability Report - Wira Nofita; Nurzi Sebrina (Jurnal Eksplorasi Akuntansi, 2023)
The purpose of this research is to examine the effect of profitability, good corporate governance and industrial type on sustainability report disclosure. The population is all companies listed in Indonesia Stock Exchange on period 2016 to 2020. By using purposive sampling method, there were 45 companies as the research sample. This research use secondary data obtained from Indonesia Stock Exchange and company's official website. The hypothesis was test using panel data analysis. The result showed that profitability, board of director, independent commissioner, audit committee and industrial type have no effect on sustainability report disclosure